2022
DOI: 10.1021/acsbiomaterials.2c00448
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Hydrogel for Prophylaxis and Early Treatment of Pressure Injuries/Pressure Ulcers

Abstract: Pressure injuries/pressure ulcers (PIs/PUs) are a critical global healthcare issue and represent a considerable burden on healthcare resources. Prevention of PIs/PUs is the least costly approach and minimizes the patient suffering compared with treatment. Besides, sustained tissue load alleviation and microenvironment management are the most crucial properties for dressings in PI/PU prevention. Hydrogel dressings have attracted a lot of attention to prevent PIs/PUs because of their unique mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…8a-h). 301 The piezoelectric gels demonstrated outstanding stretchability, skin-like ductility, and significant mechanical properties with Young's modulus values (0.48 AE 0.03 MPa) that match those of human skin (0.5-1.95 MPa). Moreover, the mechanical-electrical properties analysis revealed that the alignment of dipole moment under a certain applied pressure between acrylonitrile and PVDF resulted in the piezoelectric output characteristics.…”
Section: Polymers-based P-pegsmentioning
confidence: 94%
“…8a-h). 301 The piezoelectric gels demonstrated outstanding stretchability, skin-like ductility, and significant mechanical properties with Young's modulus values (0.48 AE 0.03 MPa) that match those of human skin (0.5-1.95 MPa). Moreover, the mechanical-electrical properties analysis revealed that the alignment of dipole moment under a certain applied pressure between acrylonitrile and PVDF resulted in the piezoelectric output characteristics.…”
Section: Polymers-based P-pegsmentioning
confidence: 94%
“…A hydrogel is a three-dimensional network of a hydrophilic polymer system with more than a 10% water content in its structure, which in turn shows good biocompatibility due to the high moisture content [ 122 ] ( Figure 8 ). Owing to its 3D matrix configuration, it not only mimics the natural ECM microenvironment but also supports cell attachment, proliferation, differentiation, regulating cell behavior, and intracellular signaling, simulating the recovery of the microenvironment of cell life properties [ 123 , 124 ]. A recent review by Ye et al [ 124 ] reported the versatility of hydrogel scaffolds for several dental purposes such as dental pulp regeneration, periodontal tissue regeneration, and drug delivery.…”
Section: Fabrication Methods/delivery Strategies For Piezoelectric Ma...mentioning
confidence: 99%
“…Li et al [ 123 ] fabricated a piezoelectric hydrogel of polyacrylonitrile-acrylamide-styrene sulfate-poly (vinylidene fluoride) (PAAN-PVDF) and reported that the fabricated PAAN-PVDF (15%) hydrogel was able to produce an output voltage close to 50 mV when the force was greater than 35 N [ 123 ]. However, it is important to note that in the case of the hydrogel matrix system, the output electrical signal resulted from two different aspects: one is the dipole moment of the piezo-material and the shape variable generated from the deformed hydrogel under certain forces.…”
Section: Fabrication Methods/delivery Strategies For Piezoelectric Ma...mentioning
confidence: 99%
See 2 more Smart Citations